Evolucija politične teorije v Sloveniji - Pikalo, Jernej (Teorija in praksa, 2022)
The article considers the development of political theory in Slovenia since 1990. The development of the discipline is presented, its roots are sought in the beginning of political theory studies in 1961 while authors, ideas, works and methodological approaches are also discussed. The article challenges the assumption that political theory studies shared a similar fate across Central and Eastern Europe, showing that there have been no breaks and divisions in political theory studies in Slovenia, but an evolution, with the next period based on the previous one. The article critically assesses the public role of political theorists, their lack of attitudes towards political theories, their responsibility and development potentia
Keywords: Politične vede